2010
DOI: 10.1111/j.1600-0714.2009.00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential infiltration of CD8+and NK cells in lip and oral cavity squamous cell carcinoma

Abstract: The differential CD8+ and NK cells infiltration in oral SCC might reflect a distinctive tumor microenvironment with a favorable local cytotoxic immune response against neoplastic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 28 publications
8
67
4
1
Order By: Relevance
“…23,27,28 In line with previous observations, Brandwein-Gensler et al 22 suggested that the lymphocytic host response to squamous cell carcinomas of the head and neck is an adaptive response mediated by cytotoxic T cells, which are found in large numbers at the interface of tumours that elicit a strong lymphocytic response (type 1).…”
Section: Discussionmentioning
confidence: 54%
“…23,27,28 In line with previous observations, Brandwein-Gensler et al 22 suggested that the lymphocytic host response to squamous cell carcinomas of the head and neck is an adaptive response mediated by cytotoxic T cells, which are found in large numbers at the interface of tumours that elicit a strong lymphocytic response (type 1).…”
Section: Discussionmentioning
confidence: 54%
“…The higher intensity of inflammation in lower lip SCCs compared to oral cavity neoplasms reported previously 24 and the downregulating effect of inflammation on ECad, 25 may help explain this finding.…”
Section: Discussionmentioning
confidence: 60%
“…Accordingly, tumors from these sites have shown considerable differences in many aspects. 23,24 Based on our results it seems that the neoplastic invasion pattern may also be considered as one of the factors that vary between these locations. The significance of this finding and its particular effect on clinical behavior of lip and oral SCCs needs to be elucidated in future studies.…”
Section: Resultsmentioning
confidence: 70%
“…T cells were associated with longer mean survival (58.2 months, 95% CI 44, 73 vs. 31.7 months, 95% CI 17, 47, Kaplan-Meier, log rank; P = 0.09) for patients with oral squamous cell carcinomas [8]. Katou demonstrated differences in the activation states between intratumoral and interface lymphocytes associated with oral squamous cell carcinoma [9].…”
Section: Discussionmentioning
confidence: 99%